FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DALAM KEHAMILAN PADA IBU HAMIL DI WILAYAH PUSKESMAS KECAMATAN PANCORAN JAKARTA SELATAN TAHUN 2022 - Fameliana Rachma Andini, (2022)
Hypertension in pregnancy is a health problem that often arises and can cause complications in 2-3% of pregnancies and is one of the 3 causes of mortality and morbidity in pregnant women. This study aims to determine the factors related to the incidence of hypertension in pregnancy in pregnant women in the Pancoran District Health Center, South Jakarta and the factors that most influence it. This study uses an analytical study design with a cross sectional approach which was carried out in April - May 2022. The population in this study were all pregnant women who live in the Puskesmas area of Pancoran District, South Jakarta with a total sample of 72 people. The sampling technique was purposive sampling and the data were analyzed by chi square test and logistic regression. The results of the analysis showed that there was a relationship between the incidence of hypertension in pregnancy and maternal age (p = 0.000), gravidity (p = 0.029), antenatal care (p = 0.000), history of hypertension (p = 0.000), obesity (p = 0.000), fat intake (p = 0.000) and sodium intake (p = 0.000) and history of hypertension were the factors that most influenced the incidence of hypertension in pregnancy (OR = 20,891). It is recommended to the puskesmas to foster cross-sectoral collaboration and conduct counseling about the risk factors and dangers of hypertension in pregnant women and it is hoped that preventive and promotive actions will be carried out by providing information facilities for pregnant women such as posters or leaflets about hypertension in pregnancy.